Review of Ethics Codes for Environmental Robots - Kim, Seonkoo (Technium Social Sciences Journal, 2023)
Like robo-fish or conservation drones, environmental robots are those that can carry out jobs for environmental research, engineering, and protection. While the term “environmental robots” can branch into robots-in-ecology, robots-for-ecology, and ecobots, each with differing purposes and ethical concerns, their overall objective is directed towards protecting and enhancing the environmental health on Earth. Though there is a huge potential for the application of environmental robots, this concept itself is relatively new, and thus there is a lack of study done on the ethical aspects of environmental robots. In past literature, researchers often focused on ‘specific’ types or products (e.g., robofish, Treebot, etc.), but there were relatively few surveys of the overall category of environmental robots. Therefore, in recent years, scholars have pointed out the need to consider wider “ethical, practical and sociopolitical concerns'' surrounding environmental robots. This paper has aimed to develop more reliable guidelines that are specific to environmental robots, considering their unique roles and characteristics. First, this paper has identified three main areas in which potential ethical issues may arise: the manufacturing of environmental robots, their operation abilities in nature and direct impact onsite, and expected or unexpected long-term consequences on ecosystems through their continued usage. Based on these three areas, the paper then built a broader guideline for the kinds of issues future ethics codes must address. Lastly, the paper systematically reviewed existing ethics codes for generic robots to suggest areas that have clear gaps or areas that are already sufficient to be applied for environmental robots. Human modification of ecosystems has been a key factor for the rapid population growth during the recent millennia, and environmental robots are growing to become the next key for this growth. However, we must proceed with attention to the design, construction, operation, and maintenance of these robots, as their positive potential for the environment may backfire and cause grave ethical concerns. Therefore, this research seeks to ultimately provide a reliable set of guidelines for future developers and manufacturers of robots associated with service in the environment.